Proposed Waste Management Concept for Equafole's Corporate Social Responsibility Program in Pangalengan - Ferdiansyah, Muhammad Nikko; Rudito, Bambang (Journal of Business and Management, 2012)
The most essential part of a cycle is a monitoring and evaluation program. Monitoring helps us to assess the position of program implementation and evaluation to help us measure the performance of our work. Secondly it helps organizations to improve performance and speed of application programs.Equafole is a profitable company that is managed by students SBM-ITB II level as a form of learning how to do business. The company is engaged in the sale of products that focus go green activity. Until now, Equafole has implemented the program for a year and kept walking. Many companies that have development programs and requires an evaluation and monitoring to improve the company's performance.In this final project, the writer wants to give some recommendations for Equafole concepts. The recommended program is generated through consideration of habits and perceptions. This final will be a guideline for improved performance.Keywords: Monitoring, Evaluation, Equafole, Community Service, students social responsibility, go green activity